The intensity of tactical technic trainings during competitive season on professional futsal athletes. - Matzenbacher, Fernando (2024)
The aim of this study was to verify and analyze the intensity of tactical technic trainings throughout the heart rate (HR) during all competitive season. Twenty professional male futsal players (age 25,6 ±4 years, weight 74,2 ±8,3 kg, height 176,9 ±6,8 cm, fat % 10,8 ±1,9 %, average distance roamed Yo-Yo intermittent recovery test level 1 of 1687 ±415 meters. 112 sessions of tactical technic trainings of a professional futsal team which played the "Liga Gaucha 1" were observed during 2019, adding up to 893 individual training sessions, checking the athletes' heart rate during the training season. The training's average duration was 63 ±15 min, and the average heart rate was 68 ± 6% HRmax; knowing that the athletes were between 25,9 ±10,5 % and 9 ±9,5 of the time in Z4 (80-90% HRmax) and in Z5 (90-100-%HRmax) during training. According ACSM (2011) the intensity of the tactical technic trainings were from moderated up to vigorous. Throughout the trainings, the athletes were about 34% of the time in Z4 and Z5 of the maximum heart rate, which is found in competitions. This percentage of the time and the intensity of the tactical technic trainings seem to be effective for athletes to have an excellent competitive performance.